PENGARUH MODEL ADVANCE ORGANIZER DENGAN PETA KONSEP UNTUK MENINGKATKAN KEMAMPUAN STRATEGIC COMPETENCE MATEMATIS SISWA SMP - Mellawaty (Universitas Wiralodra, 2016)
Strategic mathematical competence is one focus of mathematical proficiency. But in reality they encountered students who are low mathematical ability of strategic competence. One alternative learning that can improve students strategic competence mathematical is a model Advance Organizer with a concept map. This study aims to determine the increase in strategic mathematical competence capability of students who received Organizer Advance model learning with concept maps and students who obtain teaching expository method. This study used an experimental method. The population in this study were students of class VII SMP Negeri 1 Kroya Indramayu and taken two classes at random according to the class as a sample. Instruments used in this research is test the ability of strategic mathematical competence. Based on the analysis of research data, we concluded that, by enhancing the strategic competence of students who obtain a mathematical model study Advance Organizer to map the concept better than students who received learning expository method.